Development of Android-based Edutainment game on Numerical Ability - Rahanra, Nicodemus; Destari , Dina; Cakranegara, Pandu Adi; Andriyana, Erni; Ellyawati , Noor; Pratiwi, Vidya (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Learning mathematic cannot be separated from the mathematical symbol and a numerical skill, which is required as ability to perform calculation and related matters with the numbers. This research is aimed to improve the numerical ability of students. The method used was based on Borg and call, which consisted of ten main stages involved. The first research result is the validation of android-based mobile games edutainment, that is, the average value of the three experts is 78.33% with valid criteria. Then the average validation results of the android mobile game test questions based on edutainment is 77.77% with valid criteria. The second is the value of simplicity, seen from the value of the questionnaire which was filled in by all fresh graduates which was accumulated so that a percentage of 85.84% was obtained with very practical criteria. Furthermore, the effectiveness is seen from the increase in scores workmanship of fresh graduate pretest and posttest which is calculated by the formula T test results obtained by increasing the pretest posttest score then ability numerical increase so that it is categorized as effective. Thus it is concluded that the development of android mobile games is based on edutainment on numerical ability is categorized valid, practical, and effective for used